The relationship between lipid peroxidation and LDL desialylation in experimental atherosclerosis - Ozturk, Zeynep; Sonmez, Huseyin; Gorgun, F. Murat; Ekmekci, Hakan; Bilgen, Dilek; Ozen, Naile; Sozer, Volkan; Altug, Tuncay; Kokoglu, Emine (TAYLOR & FRANCIS INC, 2007)
High serum total cholesterol concentration has been strongly connected with atherosclerosis in numerous studies. Being the main carrier of cholesterol in blood, low-density lipoprotein (LDL) is also the principal lipoprotein causing atherosclerosis. Sialic acids are a family of amino sugars that are commonly found as terminal oligosaccharide residues on glycoproteins and are sialylated on their apolipoprotein and glycolipid constituents. In several studies, it was demonstrated that LDL has a 2.5- to 5-fold lower content of sialic acid in patients with coronary artery disease compared with healthy subjects. The role of oxidatively modified LDL in the pathogenesis has been well documented. These studies have focused on modifications in the lipid and protein parts of LDL. But recently, desialylated LDL and its relation with the oxidation mechanisms have received attention in the pathogenesis of atherosclerosis and coronary artery disease (CAD). From these points, we have performed atheroma plaques in an experimental atherosclerosis model with rabbits and examined the LDL and plasma sialic acid and thiobarbituric acid reactive substance (TBARS) levels in the same model. We also have determined serum sialidase enzyme activities relevant with these parameters. LDL sialic acid levels were significantly decreased in the progression of the atherosclerosis (by the 30th, 60th, and 90th days). LDL and plasma TBARS levels and plasma sialidase enzyme activities were significantly elevated by the same time periods. In conclusion, serum sialidase enzyme may play an important role in the desialylation mechanism, and reactive oxygen substance (ROS) may affect this reaction.
Keywords: atherosclerosis; LDL desialylation; sialic acid; sialidase; TBARS; LOW-DENSITY-LIPOPROTEIN; CORONARY HEART-DISEASE; SIALIC-ACID; ATHEROGENIC MODIFICATION; MACROPHAGE RECEPTOR; ENDOTHELIAL-CELLS; AORTIC-CELLS; ACCUMULATION; BLOOD; CHOLESTEROL; Toxicology